Correction: A flow focusing microfluidic device with an integrated Coulter particle counter for production, counting and size characterization of monodisperse microbubbles. Issue 10 (26th April 2019) - Rickel, J. M. Robert; Dixon, Adam J.; Klibanov, Alexander L.; Hossack, John A.
Abstract : Correction for 'A flow focusing microfluidic device with an integrated Coulter particle counter for production, counting and size characterization of monodisperse microbubbles' by J. M. Robert Rickel et al., Lab Chip, 2018, 18, 2653–2664.